Towards a Filipino Metaphysics: Particularist Narratives of Traditional Healing Practices - Espiritu, Jairus Diesta (BANWAAN: The Philippine Journal of Folklore, 2025)
Metaphysics, seen as a legitimizing narrative or a paradigm (Lyotard, 1984), prop up a certain practice in providing the basis for its assumptions. While Western medicine can be properly characterized as governed by a biophysical model (Hewa, 1994; Bates, 2002), such a model for traditional healing practices in the Philippines has yet to be derived. No philosopher has attempted to derive an indigenous metaphysics from traditional healing practices. The only study made so far (Fajardo & Pansacola, 2013), however, needlessly pigeonholes these unique practices into incommensurable Western scientific concepts. While they collated data from healers all over the country, they attempted to use Western scientific concepts such as oxygen, carbon, electro-magnetic force, and others. These concepts dangerously obfuscate indigenous understandings of the human body and reality as a whole since they are directly lifted from a language and practice informed by Western metaphysics. Therefore, there has yet to be an adequate extraction of a locally derived metaphysics that informs and self-legitimizes these medicinal practices. Conscious of recent critiques to homogenizing tendencies in Philippine Studies (Guillermo, 2009) and Filipino philosophy (Pada, 2014; Abulad, 2016), specifically that of Mercado (1972) and Timbreza (2017), I attempt to derive a Filipino metaphysics from the traditional healing practices of two traditional healers in San Mateo, Rizal of the Southern Tagalog Region in Luzon through a particularist anthropological approach in Filipino philosophy. I derive four distinct characteristics of this metaphysics which are distinct from the biophysical presuppositions of Western medicine: (1) a law of conservation based on the concept of “balik,” (2) predestination, (3) an ontological dualism between the visible and the invisible, and (4) the performativity of words as utterances. Keywords: Filipino metaphysics, traditional medicine, usog, narratives,  particularism